2011
DOI: 10.1007/s00213-011-2418-x
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine modulates both glutaminase gene expression and glutaminase activity in the brain of cocaine-sensitized mice

Abstract: The present results indicate that glutaminase enzymes (mainly KGA) are modulated by cocaine in both the prefrontal cortex and the dorsal striatum, as part of the neuroadaptions associated with behavioural sensitization to this drug of abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 48 publications
2
20
0
2
Order By: Relevance
“…This offers unique opportunities for glutamine metabolism-based therapies in the brain. One possibility derives from work by Blanco et al ., who showed that cocaine-sensitized mice exhibited a decrease in glutaminase activity in the brain, with GLS1 being altered to a much greater extent than GLS2 [58]. Although the exact patterns of changes in expression and activity varied depending upon the region of the brain examined, this still suggests that glutaminase function is affected through the use of cocaine.…”
Section: Introductionmentioning
confidence: 99%
“…This offers unique opportunities for glutamine metabolism-based therapies in the brain. One possibility derives from work by Blanco et al ., who showed that cocaine-sensitized mice exhibited a decrease in glutaminase activity in the brain, with GLS1 being altered to a much greater extent than GLS2 [58]. Although the exact patterns of changes in expression and activity varied depending upon the region of the brain examined, this still suggests that glutaminase function is affected through the use of cocaine.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the action of cocaine in noradrenergic target circuits could also contribute to the behavioral response. Elevated catecholamine transmission is a primary mediator of cocaine addiction, and repeated exposure to cocaine is associated with the recruitment of glutaminase expression and glutamatergic transmission (Glowinski and Axelrod, 1965; Cornish and Kalivas, 2000; Malenka and Bear, 2004; Lopez-Moreno et al, 2008; Ruiz et al, 2010; Blanco et al, 2012). Regarding the cerebellum, the potentiating effects of cocaine on the GABA-mediated inhibition of Purkinje neurons were not observed after the selective depletion of noradrenergic neurons (Waterhouse et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon, known as behavioral sensitization, is thought to underlie drug craving and relapse, and therefore it is one of the possible mechanisms implicated in cocaine abuse and dependence (Robinson and Berridge, ; Steketee, ). In rodents, behavioral sensitization is frequently studied using a challenge injection of cocaine in animals withdrawn from repeated cocaine administration (Blanco et al, ,b). This challenge injection elicits a higher locomotor activity than that observed in animals injected with an acute dose of cocaine, indicating a sensitized response to the drug (Kalivas and Stewart, ).…”
Section: Introductionmentioning
confidence: 99%